The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/ccd.29710
|View full text |Cite
|
Sign up to set email alerts
|

Variability in reporting of key outcome predictors in acute myocardial infarction cardiogenic shock trials

Abstract: Background: Among acute myocardial infarction patients with cardiogenic shock (AMICS), a number of key variables predict mortality, including cardiac arrest (CA) and shock classification as proposed by Society for Cardiovascular Angiography and Intervention (SCAI). Given this prognostic importance, we examined the frequency of reporting of high risk variables in published randomized controlled trials (RCTs) of AMICS patients.Methods: We identified 15 RCTs enrolling 2,500 AMICS patients and then reviewed rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 46 publications
(70 reference statements)
0
31
0
Order By: Relevance
“…have not been demonstrated to improve survival in clinical trials. 1,20 We observed some differences in the association between the use of temporary MCS (particularly the IABP) and in-hospital mortality across the clusters, which could suggest heterogeneity of MCS benefit by phenotyope; we have previously observed better outcomes with IABP use in this CS cohort. 15 If it is true that MCS devices might have greater efficacy in one of the phenotypic clusters we identified, then the inclusion of a mix of phenotypes in a clinical trial population might mask this benefit.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…have not been demonstrated to improve survival in clinical trials. 1,20 We observed some differences in the association between the use of temporary MCS (particularly the IABP) and in-hospital mortality across the clusters, which could suggest heterogeneity of MCS benefit by phenotyope; we have previously observed better outcomes with IABP use in this CS cohort. 15 If it is true that MCS devices might have greater efficacy in one of the phenotypic clusters we identified, then the inclusion of a mix of phenotypes in a clinical trial population might mask this benefit.…”
Section: Discussionmentioning
confidence: 78%
“…If the individual phenotypes have different treatment responses, then the relative prevalence of each phenotype within a theoretical clinical trial population could directly influence the magnitude and direction of the observed treatment effect 8 . It is imperative that we gain similar insights into CS populations, in whom commonly employed treatments such as temporary MCS devices have clear hemodynamic efficacy yet have not been demonstrated to improve survival in clinical trials 1,20 . We observed some differences in the association between the use of temporary MCS (particularly the IABP) and in‐hospital mortality across the clusters, which could suggest heterogeneity of MCS benefit by phenotyope; we have previously observed better outcomes with IABP use in this CS cohort 15 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…21 The other key variable is the presence of cardiac arrest, as many patients die of neurological injury and not cardiac dysfunction. 22 However, such a trial would require large numbers of patients, and would not be neatly defined like the described trials with ACS CS.…”
mentioning
confidence: 99%
“…The way forward is to conduct trials involving an ‘all‐comers’ population, and stratify by severity of shock (perhaps by prospectively assigning Society for Cardiac Angiography and Intervention Shock Stage, SCAI) 21 . The other key variable is the presence of cardiac arrest, as many patients die of neurological injury and not cardiac dysfunction 22 . However, such a trial would require large numbers of patients, and would not be neatly defined like the described trials with ACS CS.…”
mentioning
confidence: 99%